Analisis Variabel-Variabel yang Memengaruhi Kemiskinan di Nusa Tenggara Timur Tahun 2023 - F, Fatimatuzzuhra; Purwoto, Agus; Ikhsan, Muh. Ruhul; Siregar, Revina; Khairunnisak, Zahra (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the main problems in Indonesia is poverty. According to the Indonesian Central Statistical Agency, by 2023, East Nusa Tenggara Province (NTT) is one of the provinces with a high number of poor people with a total of 1.1 million poor people. The causes of high poverty in East Nusa Southeast province need to be investigated. The study aims to find out the general picture of poverty and the variables that are supposed to affect it, as well as the significant variables affecting poverty in East Nusa Tenggara Province in 2023. The method used in the research is multiple linear regression. The results of the analysis showed that the economic growth variable (PDRB) and the unemployment rate (TPT) had a negative and significant impact on poverty, while education (average school age) and human development index (IPM) had no significant impact. The R-square value of this study is 0.567 which means that 56.7 percent of the diversity of the poverty variable can be explained by the economic growth variables, education, the human development index, and the unemployment rate, while the remaining 43.3 percent are described by other variables that do not fit into the model.